Development of the FAST‐M maternal sepsis bundle for use in low‐resource settings: a modified Delphi process. (5th December 2019) - Lissauer, D; Cheshire, J; Dunlop, C; Taki, F; Wilson, A; Smith, JM; Daniels, R; Kissoon, N; Malata, A; Chirwa, T; Lwesha, VM; Mhango, C; et al.
Abstract : Objective: To develop a sepsis care bundle for the initial management of maternal sepsis in low resource settings. Design: Modified Delphi process. Setting: Participants from 34 countries. Population: Healthcare practitioners working in low resource settings ( n = 143; 34 countries), members of an expert panel ( n = 11) and consultation with the World Health Organization Global Maternal and Neonatal Sepsis Initiative technical working group. Methods: We reviewed the literature to identify all potential interventions and practices around the initial management of sepsis that could be bundled together. A modified Delphi process, using an online questionnaire and in‐person meetings, was then undertaken to gain consensus on bundle items. Participants ranked potential bundle items in terms of perceived importance and feasibility, considering their use in both hospitals and health centres. Findings from the healthcare practitioners were then triangulated with those of the experts. Main outcome measure: Consensus on bundle items. Results: Consensus was reached after three consultation rounds, with the same items deemed most important and feasible by both the healthcare practitioners and expert panel. Final bundle items selected were: (1) Fluids, (2) Antibiotics, (3) Source identification and control, (4) Transfer (to appropriate higher‐level care) and (5) Monitoring (of both mother and neonate as appropriate). The bundle was given the acronym 'FAST‐M'. Conclusion: A clinically relevant maternal sepsis bundle for low resource settings has been developed by international consensus. Tweetable abstract: A maternal sepsis bundle for low resource settings has been developed by international consensus. Tweetable abstract: A maternal sepsis bundle for low resource settings has been developed by international consensus.